2014
DOI: 10.1590/s1517-83822014000300004
|View full text |Cite
|
Sign up to set email alerts
|

Conjugative transfer of resistance determinants among human and bovine Streptococcus agalactiae

Abstract: Streptococcus agalactiae (GBS) is a major source of human perinatal diseases and bovine mastitis. Erythromycin (Ery) and tetracycline (Tet) are usually employed for preventing human and bovine infections although resistance to such agents has become common among GBS strains. Ery and Tet resistance genes are usually carried by conjugative transposons (CTns) belonging to the Tn916 family, but their presence and transferability among GBS strains have not been totally explored. Here we evaluated the presence of Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
10
11
0
Order By: Relevance
“…Isolates 243 and 322, were both erythromycin sensitive however, at least one gene ermTR or mefA was found, respectively (see Additional le 2: Table S2 and S3). Similar ndings were reported in GBS and other streptococcal species (64,(66)(67)(68). A con rmatory test to check Minimum Inhibitory Concentration (MIC) levels of these three isolates is recommended.…”
Section: Unexpressed Resistant Genotypessupporting
confidence: 69%
See 1 more Smart Citation
“…Isolates 243 and 322, were both erythromycin sensitive however, at least one gene ermTR or mefA was found, respectively (see Additional le 2: Table S2 and S3). Similar ndings were reported in GBS and other streptococcal species (64,(66)(67)(68). A con rmatory test to check Minimum Inhibitory Concentration (MIC) levels of these three isolates is recommended.…”
Section: Unexpressed Resistant Genotypessupporting
confidence: 69%
“…It was also observed that 100% (n=10) isolates that carried the ermB gene also carried the tetM gene. The association of erythromycin and tetracycline resistance may be due to the conjugative transposon Tn1545, which encodes erythromycin resistance via the ermB gene and tetracycline resistance via the tetM gene (62)(63)(64). This association was supported by our analysis which showed a positive correlation (see Additional le 2: Table S5) between the two genes, but this lacked statistical signi cance according to the Spearman Rank test.…”
Section: Genetic Linkage In Macrolide/tetracycline Resistance Determimentioning
confidence: 53%
“…These are the most commonly identified tet genes among both bovine and human S. agalactiae isolates (DOGAN et al, 2005;DUARTE et al, 2005;DUTRA et al, 2014;PINTO et al, 2014), while others determinants such as tetS and tetK being observed less frequently (DUARTE et al, 2004;RATO et al, 2013). Four isolates exhibiting phenotypic tetracycline resistance harbored neither tetM nor tetO, suggesting the presence of a different tet gene, such as tetS or tetK.…”
Section: Discussionmentioning
confidence: 98%
“…Accordingly, certain ELISA detection methods have been established based on these relatively conserved single antigens, but the sensitivities of the methods targeting one single conserved antigen are not sufficiently high (Keefe 1997, Pinto et al 2014). In our previous study, we used the DNAstar software to analyze the antigen epitope sequences of Sip, Pgk, and FbsA3 of SA, respectively, and the dominant antigen genes of these three proteins were amplified and concatenated by overlap-extension PCR, followed by expression and purification to ultimately obtain the recombinant multi-subunit fusion protein rSip-Pgk-FbsA.…”
Section: Discussionmentioning
confidence: 99%